Konflik Hak Cipta di Balik Naskah Film Soekarno - Siregar, Bismar (DOKTRINA: JOURNAL OF LAW, 2025)
This research discusses the copyright conflict between Rachmawati Soekarnoputri and PT Tripar Multivision Plus and director Hanung Bramantyo regarding the film Soekarno. The main focus of the study is the violation of moral and economic rights over film scripts which are claimed to be Rachmawati's creation. The method used is normative legal research with a descriptive-analytical approach, which is based on a study of Supreme Court Decision No. 305 K/Pdt.Sus-HKI/2014. The research results show that there is an element of breach of contract regarding the creator's moral rights because Rachmawati's name is not included as the script writer. However, the Supreme Court was of the opinion that Soekarno's life could not be claimed as an individual copyrighted work and no formal legal copyright infringement had been proven. These findings highlight the gaps in legal protection for works based on biographies of public figures and the importance of formal proof in copyright disputes.